Beyond a Legacy of Coercion: Long-Acting Reversible Contraception (LARC) and Social Justice. Issue 1 (2nd January 2019) - Meier, Stephanie; Sundstrom, Beth; DeMaria, Andrea L.; Delay, Cara
Abstract: One half of all pregnancies in the United States are unintended. The American College of Obstetricians and Gynecologists has recommended long-acting reversible contraception (LARC) as first-line pregnancy prevention for all women and adolescent girls. However, continued reproductive coercion in the U.S., especially among underserved populations, problematizes the promotion of LARC methods. We conducted six focus groups ( n = 61) and 18 interviews with women ages 18–44 years to explore the impact of coercion on women's perspectives of LARC methods and messages about LARC. Findings suggest the importance of identity in how women make meaning of LARC methods. Identification with women who use LARC methods influenced participants' understanding of contraceptive choice. Lack of information provided by health care providers about LARC served as a barrier to method knowledge. Findings from this study offer theoretical and practical opportunities to guide health care practitioners and health communication campaigns aimed at decreasing the burden of unintended pregnancy while maintaining reproductive justice.